Kajian Ekranisasi Novel Rembulan Tenggelam di Wajahmu Karya Tere Liye dan Film Rembulan Tenggelam di Wajahmu Sutradara Danial Rifki - Noni Andriyani; Chintiya, Chintiya (UIR PRESS, 2021)
Ecranization is a study that discusses the transfer of the whitewashing of the novel into the film. The problems contained in this research, namely: how is the process of ecranization of the shrinking aspect in the novel Rembulan Tenggelam di Wajahmu? How is the process of ecranization of additional aspects in the novel and film Rembulan Tenggelam di Wajahmu? How is the process of ecranizing the various aspects of change in the novels and films of Rembulan Tenggelam di Facemu? This study aims to determine: the process of ecranization of the shrinking aspect in the novel and film Rembulan Tenggelam di Facemu; The process of ecranization of additional aspects in the novel and film Rembulan Tenggelam di Wajahmu; The process of ecranization of aspects of change varies from novels and films Rembulan Tenggelam di Wajahmu. This research includes library research (Library research). This study uses a qualitative method. Data collection techniques using hermeneutic techniques and observations. The theory used is the theory of Eneste (1991). The results of the study: (1) Aspects of shrinkage there are 97 data that occur in the elements of the plot, characters, and setting of the novel. Such as the absence of 3 characters Rinai, Beverage Trader, Qolu in the novel; (2) Aspects of addition there are 21 data that occur in the elements of plot, character, and film setting. As added scene 1, the characters of Sister and Doctor in the film; (3) Aspects of change vary, there are 34 data that occur in plot elements, characters, and novel settings. Like the changing setting of the atmosphere during the Eid prayer which depicts the caretaker of the orphanage and the orphanage children going to celebrate the takbiran night, while in the novel they go to the field for the Id prayer. The ecranization process causes shrinkage, addition, and various changes. This happens because of the differences in the media used in the making of novels and films, differences in the production process, and differences in the enjoyment process.